2012
DOI: 10.1128/aac.05993-11
|View full text |Cite
|
Sign up to set email alerts
|

An Isoniazid Analogue Promotes Mycobacterium tuberculosis-Nanoparticle Interactions and Enhances Bacterial Killing by Macrophages

Abstract: g Nanoenabled drug delivery systems against tuberculosis (TB) are thought to control pathogen replication by targeting antibiotics to infected tissues and phagocytes. However, whether nanoparticle (NP)-based carriers directly interact with Mycobacterium tuberculosis and how such drug delivery systems induce intracellular bacterial killing by macrophages is not defined. In the present study, we demonstrated that a highly hydrophobic citral-derived isoniazid analogue, termed JVA, significantly increases nanoenca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 48 publications
3
35
1
1
Order By: Relevance
“…Our data show that when either mouse primary macrophages or RAW cells were infected with red BCG and allowed to internalize the coumarin-6 green-labeled particles, there was no evident colocalization between the bacteria and the PLGA particles. This result is in agreement with the conclusions made by (Kisich et al, 2007), but at odds with the findings of (de Faria et al, 2012) who concluded that PLGA NPs enclosing an isoniazid derivative directly interacts with the BCG phagosomes in macrophages. Earlier studies had established that BCG, like M.tb, resides in an arrested early phagosome stage, with only a small fraction of phagosomes acquiring markers of lysosomes.…”
Section: Discussioncontrasting
confidence: 50%
“…Our data show that when either mouse primary macrophages or RAW cells were infected with red BCG and allowed to internalize the coumarin-6 green-labeled particles, there was no evident colocalization between the bacteria and the PLGA particles. This result is in agreement with the conclusions made by (Kisich et al, 2007), but at odds with the findings of (de Faria et al, 2012) who concluded that PLGA NPs enclosing an isoniazid derivative directly interacts with the BCG phagosomes in macrophages. Earlier studies had established that BCG, like M.tb, resides in an arrested early phagosome stage, with only a small fraction of phagosomes acquiring markers of lysosomes.…”
Section: Discussioncontrasting
confidence: 50%
“…The active INH content of the NPs could in future be adjusted to an effective concentration that takes into consideration both the slow drug releasing nature of the PLGA particle and the degree of targetting achievable by the MA ligandation. The concentrations of INH in the particles used for the EM observations were approximately 5 μg/ml in the preparation medium, ten times less than a recent in vitro study of an INH analogue that was tested in PLGA particles [47]. As mentioned before, INH-PLGA NPs have shown sustained drug release over several days in vitro and in vivo [66] and allowed a reduction in treatment frequency in mice and guinea pig models [67][68][69].…”
Section: Discussionmentioning
confidence: 94%
“…Another issue is the ability for PLGA particles to reach the compartment in which mycobacteria reside. One group suggested this possibility [47], but others could not demonstrate it [10,45].…”
Section: Introductionmentioning
confidence: 96%
“…Bacterial concentration was determined by a number 1 McFarland scale equivalent to 3 × 10 8 bacteria/mL. The INH resistance phenotype of 255R was confirmed by experiments employing a previously described MTT protocol [66], which revealed that the minimal inhibitory concentration (MIC) of 255R is 30 times higher than the H37Rv MIC. Presence of the functionally impaired S315T katG mutation was detected by sequencing.…”
mentioning
confidence: 99%